Effect of layer thickness and cross-section geometry on the tensile and compression properties of 3D printed ABS. (March 2020) - Nomani, Junior; Wilson, Daniel; Paulino, Mariana; Mohammed, Mazher Iqbal
Abstract: This study examines the influence of deposition layer thickness on the mechanical properties of printed ABS material when manufacturing using Fused Filament Fabrication (FFF). Tensile and compression testing was performed to ASTM standards on samples printed with layer thickness between 0.2 mm and 0.8 mm. Results found material strength and stiffness was greatest using smaller layer thicknesses, compared with larger layer thicknesses e.g. σ y ( 0.2 m m ) = 31.5 MPa, U T S 0.2 m m = 38.2 MPa, compared with σ y ( 0.8 m m ) = 23.0 MPa, U T S 0.8 m m = 31.0 MPa. The recorded changes in mechanical properties are explained by mechanisms relating to manufacturing residual porosity, the number of deposited layers promoting interlayer bonding strength, and the extrusion process resulting in material shear hardening. Findings have implications on the ability to reduce the overall part print time using a method of increased material deposition, and may have profound implications on comparative part integrity when utilising large volume deposition printing formats with unmodified ABS polymer. The findings from this study also highlight the need for current mechanical testing standards to accommodate appropriate guidelines for the testing of 3D printed material, given the wide variance of measured tensile and compression properties based on layer thickness and printed geometry.